Heat exciton type organic glass scintillator material and preparation method and application thereof

By combining the heat exciton-type high-efficiency luminescent guest material and the glass main material, the heat exciton-type plexiglass scintillator material was developed, which solved the difficulties in the preparation and application of X-ray scintillator materials in the prior art, and achieved efficient X-ray luminescence and high-quality imaging.

CN119875624AActive Publication Date: 2025-04-25XIAMEN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510294828.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-13
Publication Date
2025-04-25
Estimated Expiration
2045-03-13

AI Technical Summary

Technical Problem

The existing X-ray scintillator materials have high temperature requirements, long growth cycles, low exciton utilization, low radiation blocking ability and large-area processing difficulties in preparation and application, which limits their application in X-ray imaging and other fields.

Method used

A thermal exciton-type plexiglass scintillator material was developed to achieve efficient radiative luminescence by combining thermal exciton-type efficient luminescent guest material with specific glass main material, using the thermal exciton mechanism to achieve efficient radiative luminescence, and to prepare high-quality scintillator films by precisely controlling the doping ratio and melt heating procedures.

Benefits of technology

It has achieved efficient X-ray luminescence, short attenuation life, large-area processing capability, amorphous transparency and stability, significantly improving the photoluminescence quantum efficiency and imaging resolution, and is suitable for medical diagnosis, safety detection and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875624A_ABST
    Figure CN119875624A_ABST
Patent Text Reader

Abstract

The invention discloses a heat exciton type organic glass scintillator material as well as a preparation method and application thereof. The heat exciton type organic glass scintillator material comprises a glass host material and a heat exciton type efficient luminous guest material. The heat exciton type organic glass scintillator material can be efficiently prepared through accurate temperature control and simple melting processing means, and has the advantages of high transparency, large area and stable performance. The heat exciton type organic glass scintillator material has more than 95% of photoluminescence quantum efficiency and nanosecond-level attenuation life, and meanwhile, can show efficient radiation luminescence performance, extremely low detection limit and relatively high imaging resolution under excitation of X-rays, and can be applied to the field of X-ray imaging, such as X-ray imaging, X-ray imaging, X-ray imaging, X-ray imaging, X-ray imaging, X-ray imaging, X-ray imaging and X-ray imaging. Due to the characteristics, the method has extremely wide application prospects in the fields of medical diagnosis and treatment, safety inspection, industrial nondestructive testing and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of luminescent materials, and mainly to a thermoexciton organic glass scintillator material and a preparation method and application thereof. Background Art

[0002] X-ray scintillators are a type of material that has luminescent properties when excited by X-rays, and can convert high-energy X-rays into low-energy visible light. With this unique property, X-ray scintillators can be used in key areas such as radiation detection, safety testing, and biomedicine, and have received widespread attention. However, most of the X-ray scintillators widely used in business are inorganic materials represented by ceramic scintillators. These inorganic scintillator materials usually need to be prepared under high temperature conditions and are often accompanied by a long growth cycle, making it difficult to achieve large-area, high-performance scintillators through economical and easily replicable methods.

[0003] Pure organic light-emitting materials have attracted much attention because they do not contain metal elements and have significant advantages such as abundant raw material reserves, high mechanical flexibility, excellent processing performance, and easy synthesis and modification. However, there are some fundamental limitations in the practical application of organic scintillator materials, mainly manifested in low exciton utilization and low radiation blocking ability inherent to low atomic number. Traditional organic fluorescent molecules can only utilize 25% of singlet excitons, and although thermally activated delayed fluorescence and phosphorescent materials can increase the scintillation light yield, their delayed fluorescence or phosphorescent process will cause the scintillation lifetime to be extended to microseconds or even seconds, which is not conducive to the imaging application of scintillators. Thermionic materials achieve non-delayed fluorescence by "manipulating" thermal excitons, and have the advantages of high exciton utilization and fast time decay, which can effectively circumvent the dilemma of traditional organic scintillators.

[0004] In addition, currently, large-sized organic scintillator single crystals (>1 cm) are mainly grown. 2 ) or doping scintillator microcrystals (5-60wt%) into a polymer matrix to form a scintillator film to achieve X-ray imaging. However, the former requires a long single crystal growth process and is difficult to control in thickness and size, which severely limits its application; although the latter can prepare large-area films, it significantly reduces the content of organic scintillator, resulting in a decrease in the intensity of radiation luminescence, and the matrix usually has limited X-ray absorption capacity. In addition, high doping levels often make the film opaque, causing optical scattering, which seriously affects the imaging effect.

[0005] Therefore, the development of a new type of hot exciton-type pure organic scintillator material with efficient X-ray luminescence, short decay lifetime, large-area processing capability, amorphous transparency and stability has important practical significance and application value. Summary of the invention

[0006] In view of the technical problems existing in the prior art, the present application proposes a thermoexciton organic glass scintillator material and a preparation method and application thereof.

[0007] According to one aspect of the present invention, a thermoexciton organic glass scintillator material is provided, comprising a glass main material and a thermoexciton high-efficiency luminescent guest material; the glass main material comprises or The hot exciton type high efficiency luminescent guest material includes , , or .

[0008] Thermoexciton-type luminescent guest materials can make full use of high-energy triplet excitons and convert triplet excitons into singlet excitons through reverse intersystem crossing, thereby achieving efficient radiative luminescence. By combining the thermoexciton-type efficient luminescent guest materials with specific glass host materials, the thermoexciton mechanism is fully utilized to achieve efficient radiative luminescence, which can significantly improve the photoluminescence quantum efficiency while maintaining the transparency and large-area processing capabilities of the material, providing a high-performance organic scintillator material for fields such as X-ray imaging.

[0009] In a specific embodiment, the glass main body material has excellent thermal stability, photoelectric performance and film-forming properties, which can ensure that the thermoexciton organic glass scintillator material operates stably in a high temperature environment, improve its service life and reliability, and ensure that the final product forms a large-area, uniform thin film. In addition, the glass main body material also has excellent biocompatibility, which makes the scintillator material have great development potential in the biomedical field.

[0010] In a specific embodiment, the above-mentioned thermoexciton-type luminescent guest material has high luminescence efficiency, fast luminescence decay characteristics, good thermal stability and biocompatibility, etc., and can perfectly cooperate with the above-mentioned glass host material to form a thermoexciton-type organic glass scintillator material with excellent performance and broad application prospects.

[0011] Preferably, R in the glass main material includes H, F, Cl, Br, I or CH3.

[0012] In a specific embodiment, different R groups will affect the energy level structure of the molecule, and thus affect the optical properties of the glass host material; at the same time, different R groups will also affect the solubility, biocompatibility and mechanical properties of the glass host material. By rationally selecting and designing the R groups, the chemical properties and physical properties of the glass host material can be adjusted, and its interaction with the thermoexciton-type luminescent guest material can be further optimized, so as to better match the energy transfer requirements of the luminescent guest, reduce energy loss, and further improve the luminescence efficiency and stability of the material.

[0013] Preferably, X in the thermoexciton type high-efficiency light-emitting guest material includes N or P.

[0014] In a specific embodiment, the atomic radius of N atoms is small, the electronegativity is high, and they usually form strong covalent bonds in compounds, with high bond energy and stability, while the atomic radius of P atoms is large, the electronegativity is low, and the bonds formed in compounds are usually weak, and the compounds tend to show greater steric hindrance effects. By selecting N or P, the electronic structure and energy level distribution of the luminescent guest can be adjusted, thereby optimizing its thermal exciton utilization efficiency and luminescence intensity, so that the material can emit visible light more efficiently under X-ray excitation, and improve imaging quality.

[0015] Preferably, R1 in the thermoexciton-type high-efficiency luminescent guest material comprises , , , or .

[0016] In a specific embodiment, different R1 groups affect the stacking and π-π interaction between molecules, and thus affect the crystallinity and molecular order of the thermoexciton-type high-efficiency luminescent guest material, which is crucial to improving the luminous efficiency and stability of the product. In addition, the R1 group also affects the luminescent wavelength and color, thermal stability, solubility, mechanical properties and biocompatibility. By rationally selecting and designing the R1 group, the desired properties can be brought to the glass host material to meet the needs of different application scenarios.

[0017] Preferably, R2 in the thermoexciton-type high-efficiency luminescent guest material comprises H, F, Cl, Br or I.

[0018] In a specific embodiment, different halogen atoms have different atomic radii and electronegativity. By introducing different R2 groups, the electronic properties and intermolecular interactions of the thermoexciton-type luminescent guest material can be adjusted, thereby affecting its exciton formation and energy transfer process. At the same time, different halogen atoms can achieve the adjustment of X-ray absorption. In addition, selecting different R2 groups can optimize the luminescence efficiency and decay life of the thermoexciton-type high-efficiency luminescent guest material, so that it exhibits faster time response and higher imaging clarity in X-ray imaging.

[0019] According to a second aspect of the present invention, a method for preparing a thermoexciton organic glass scintillator material is proposed, which specifically comprises the following steps: S1, doping the thermoexciton type luminescent guest material into the glass main material to obtain a mixture, wherein the mass ratio of the thermoexciton type luminescent guest material to the glass main material is 0.001%-6%; S2, placing the mixture on a silica gel substrate to melt, the melting temperature program is: first heating to 160 ° C and keeping it for 5 min, then heating by 10 ° C every 3 min until the temperature reaches the preset melting temperature; S3, the mixture is completely melted, stirred until no bubbles are generated, and then kept warm for 5 minutes, and then naturally cooled to room temperature to obtain a thermoexciton type organic glass scintillator film material.

[0020] This method can achieve uniform doping and high-quality film preparation by precisely controlling the doping ratio of the hot exciton luminescent guest material and the glass host material and the melting temperature program. This method is simple and easy to implement, suitable for large-area processing, and can effectively avoid the problems of slow single crystal growth and opaque films in traditional preparation methods, thereby improving the preparation efficiency and imaging performance of the material.

[0021] In a specific embodiment, the thickness of the thermoexciton organic glass scintillator film material manufactured by this method is 0.5-3 mm.

[0022] Preferably, in S1, the mass ratio of the thermoexciton type luminescent guest material to the glass host material is 0.001%, 0.01%, 0.1%, 0.5%, 2%, 4% or 6%.

[0023] In a specific embodiment, different doping ratios will affect the generation and recombination efficiency of excitons, thereby affecting the luminescence efficiency; different doping ratios will also affect the energy level structure of the material, thereby affecting the luminescence wavelength and color; at the same time, a suitable doping ratio helps to form a uniform film. By selecting a suitable ratio, the material can achieve the best performance balance in X-ray imaging while ensuring the transparency and stability of the material.

[0024] Preferably, in S2, the melting heating device is a heating block.

[0025] In a specific embodiment, the heating block can achieve precise temperature control, provide a stable and uniform heating environment, help maintain the integrity of temperature-related reactions, avoid quality problems caused by local overheating or overcooling, thereby improving the quality and uniformity of the film and ensuring the consistency and repeatability of experimental results.

[0026] Preferably, in S2, the melting temperature is 180-220°C.

[0027] In a specific embodiment, the melting temperature is determined according to the melting points of the selected glass host material and the thermoexciton-type luminescent guest material. Within this temperature range, the mixture can be fully melted while avoiding decomposition of the material or degradation of its performance due to excessively high temperatures, thereby ensuring the stability and repeatability of the preparation process and ensuring that the optical and mechanical properties of the material are not affected, thereby helping to achieve high-quality organic glass scintillator films.

[0028] According to a third aspect of the present invention, a use of a thermoexciton organic glass scintillator material in X-ray imaging is proposed.

[0029] The thermoexciton organic glass scintillator material has high X-ray luminescence, short decay life, large-area processing capability, amorphous transparency and good stability, which can significantly improve the performance of X-ray imaging equipment. Its application in X-ray imaging can achieve higher imaging resolution, lower detection limit and better stability, which has important practical significance and broad application prospects in the fields of medical diagnosis, safety detection, etc.

[0030] Compared with the prior art, this application has the following beneficial effects: The solution of the present application can efficiently prepare a scintillator film with high transparency, large area and stable performance through precise temperature control and simple melting processing means, and the thermoexciton organic glass scintillator material has low cost and can be industrialized. The thermoexciton organic glass scintillator material of the present application has a photoluminescence quantum efficiency of more than 95% and a decay lifetime of nanoseconds, which makes it show great application potential in the field of dynamic imaging and can significantly improve image clarity; The thermoexciton organic glass scintillator material of the present application exhibits efficient radioluminescence performance, extremely low detection limit and high imaging resolution under X-ray excitation. These characteristics give it extremely broad application prospects in many fields such as medical diagnosis and treatment, safety inspection and industrial non-destructive testing, and is expected to bring technological innovation to related industries and improve detection efficiency and accuracy. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings are included to provide a further understanding of the embodiments and are incorporated into and constitute a part of this specification. The accompanying drawings illustrate the embodiments and are used together with the description to explain the principles of the present invention. It will be easy to recognize other embodiments and many expected advantages of the embodiments because they become better understood by reference to the following detailed description. The elements of the drawings are not necessarily to scale with each other. The same reference numerals refer to corresponding similar parts.

[0032] Figure 1A schematic diagram of a manufacturing process of a thermoexciton type organic glass scintillator material according to an embodiment of the present invention is shown; Figure 2 shows a photoluminescence spectrum diagram according to a specific embodiment of the present invention; Figure 3 A fluorescence decay curve diagram according to a specific embodiment of the present invention is shown; Figure 4 A diagram showing the relationship between Stokes shift and solvent orientation polarization according to a specific embodiment of the present invention is shown; Figure 5 shows a luminescence spectrum diagram under X-ray irradiation according to a specific embodiment of the present invention; Figure 6 shows a statistical diagram of photoluminescence quantum efficiency according to a specific embodiment of the present invention; Figure 7 shows a transmission spectrum diagram according to a specific embodiment of the present invention; Figure 8 shows an X-ray detection limit spectrum according to a specific embodiment of the present invention; Fig. 9 An X-ray imaging photograph and an X-ray imaging resolution diagram according to a specific embodiment of the present invention are shown; Fig.10 shows a stability spectrum under X-ray irradiation according to a specific embodiment of the present invention; Fig.11 shows a luminescence spectrum diagram under X-ray irradiation according to another specific embodiment of the present invention; Fig.12 A luminescence spectrum diagram under X-ray irradiation according to another specific embodiment of the present invention is shown. DETAILED DESCRIPTION

[0033] The present application will be further described in detail below in conjunction with the accompanying drawings and embodiments. It is to be understood that the specific embodiments described herein are only used to explain the relevant invention, rather than to limit the invention. It should also be noted that, for ease of description, only the parts related to the relevant invention are shown in the accompanying drawings.

[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0035] Figure 1 A schematic diagram of the production process of a thermoexciton organic glass scintillator material is shown. Figure 1 The specific production process is as follows: S1, doping a thermoexciton-type luminescent guest material into a glass host material to obtain a mixture, wherein the mass ratio of the thermoexciton-type luminescent guest material to the glass host material is 0.001%-6%; S2. Place the mixture on a silica gel substrate to melt. Select an 8 ml × 16-well heating block to precisely control the temperature on the heating table. The melting temperature program is: first heat to 160 °C for 5 min, then increase the temperature by 10 °C every 3 min until the temperature reaches the preset melting temperature. S3. The mixture is completely melted, stirred until no bubbles are generated, and then kept warm for 5 minutes, and then naturally cooled to room temperature to obtain a thermoexciton type organic glass scintillator film material. Example 1

[0036] A thermoexciton organic glass scintillator material, comprising a glass main material ( m CP) and hot exciton luminescent guest material (N-BA), the molecular structures are: and .

[0037] m The NMR characterization results of CP are as follows: 1 H NMR (DMSO-d6) δ (ppm) 7.56 (d, J =8.8Hz, 4H),7.34-7.23 (m, 2H), 7.11-7.03 (m, 1H), 6.75 (d, J =8.8Hz, 4H).

[0038] The preparation route of N-BA is as follows: (1) (2) In formula (1), the NMR characterization results of 9, 10-bis (4-bromophenyl) anthracene are as follows: 1 H NMR (600 MHz, DMSO-d6): δ(ppm) 7.87 (4H, d, J = 7.2 Hz); 7.59-7.57 (4H, m); 7.47 (4H, m); 7.44 (4H, d, J = 7.32 Hz).

[0039] The specific preparation process of formula (2) 4, 4'-(anthracene-9,10-diyl) bis (N-butyl-N-phenyl) dianiline is as follows: in an inert gas atmosphere, 9,10-bis(4-bromophenyl)anthracene (0.55 mmol), 2-(di-tert-butylphosphino)biphenyl (CAS: 224311-51-7, 0.05 mmol), tris(dibenzylideneacetone)dipalladium (CAS: 51364-51-3 0.02 mmol) and sodium tert-butoxide (CAS: 865-48-5, 2.20 mmol) were mixed in a flask, and then N-butylaniline (CAS: 1126-78-9, 1.65×10 − 3 mol) and toluene. The reaction mixture was stirred under nitrogen and refluxed at 85-120 °C for 12 h. After the reaction was completed, it was extracted with saturated brine, dried over anhydrous magnesium sulfate, and the solvent was removed by rotary evaporation. The crude product was purified by column chromatography (petroleum ether: dichloromethane: 4:1), recrystallized and vacuum dried to obtain a green solid product N-BA (87.9%), and its NMR characterization results are as follows: 1 HNMR (400MHz, CDCl3): δ 7.86–7.82 (m, 4H), 7.39–7.31 (m, 12H), 7.23 (d, J = 7.8Hz, 4H), 7.15 (d, J = 8.4 Hz, 4H), 7.05 (t, J = 7.4 Hz, 2H), 3.86–3.81 (m, 4H), 1.82–1.77 (m, 4H), 1.47–1.43 (m, 4H), 1.00 (t, J = 7.4 Hz, 6H).

[0040] based on m CP and N-BA thermoexciton organic glass scintillator film (N-BA@ m The production process of CP is as follows: S11, take 0.1 g m CP was mixed with 0.001 mg of N-BA to obtain a mixture; S12, place the mixture on a 3×3 cm circular silica gel substrate, select an 8 ml×16-well heating block to accurately control the temperature on the heating table, and the melting temperature program is: first heat to 160 ℃ and keep warm for 5 min, then increase the temperature by 10 ℃ every 3 min and keep warm for 2 min, and finally heat to 190 ℃; S13, waiting for the mixture to be completely melted, stirring until no bubbles are generated, and then keeping the mixture warm for 5 minutes, and then naturally cooling it to room temperature to obtain a thermoexciton organic glass scintillator film.

[0041] Repeat the above steps and take 0.1 g of m CP was mixed with 0.01 mg, 0.1 mg, 0.5 mg, 2 mg, 4 mg and 6 mg of N-BA, melted and cooled to obtain another 6 groups of thermoexciton-type organic glass scintillator film samples.

[0042] Figure 2 N-BA crystalline sample, N-BA glassy sample, and 2 wt% N-BA@ m Photoluminescence spectra of CP samples under X-ray irradiation. Figure 2 It can be seen that the characteristic emission peaks of the three samples are all located around 500 nm, showing green luminescence.

[0043] Figure 3 N-BA crystalline sample, N-BA glassy sample, and 2 wt% N-BA@ m Fluorescence decay curve of CP sample, from Figure 3 As can be seen in the figure, all samples exhibit very fast nanosecond decay lifetimes, which means that the material will not have afterimages when used in the field of X-ray imaging.

[0044] Figure 4 is the relationship between Stokes shift and solvent orientation polarization of N-BA, such as Figure 4 As shown, combined with the changes in the emission spectrum and absorption spectrum of N-BA molecules in different polar solvents, using the Lippert-Mataga model based on Stokes shift and solvent orientation polarizability, it can be found that the fitting line of Stokes shift of N-BA and solvent polarity (f) shows two different slopes, which indicates that there are two different excited states: the local excited state (LE) in low polarity solvents and the charge transfer state (CT) in high polarity solvents.

[0045] In summary, Figure 2-4 It is proved that N-BA molecule has the emission characteristics of HLCT state, making it an organic hot exciton molecule.

[0046] Figure 5 7 groups of hot exciton organic glass scintillator samples and undoped luminescent guest materials m The radiative luminescence spectrum of the CP sample is shown in Figure 2. Figure 5As shown in the figure, under X-ray excitation, the seven groups of thermoexciton organic glass scintillator samples all showed an obvious characteristic emission peak near 500 nm, and the intensity of the characteristic emission peak increased significantly with the increase of the doping concentration of the luminescent guest material. m The CP sample has almost no luminescence near 500 nm, which indicates that the luminescence of the thermoexciton organic glass scintillator mainly comes from the thermoexciton luminescent guest material.

[0047] Figure 6 The photoluminescence quantum efficiency statistics of 7 groups of thermoexciton organic glass scintillator samples are shown in Figure 2. Figure 6 As shown in the figure, all seven groups of thermoexciton organic glass scintillator samples showed high photoluminescence quantum efficiency. Among them, the photoluminescence quantum efficiency of the scintillators with doping mass ratios of 0.001% and 0.01% was lower than that of other samples. When the doping mass ratio increased to 0.1%, the photoluminescence quantum efficiency was significantly improved, reaching 97.7%.

[0048] In a specific embodiment, a 2 wt% N-BA@ based on a flexible silicone substrate was prepared by a heating block temperature controlled melting method. m Scintillation screen of CP (2.5 mm diameter, 1 mm thickness). Figure 7 is 2 wt%N-BA@ m CP scintillation screen and glass body material m The transmission spectrum of CP is shown in Figure 7 As shown, the thermoexciton organic glass scintillating screen has good transparency and a transmittance greater than 80% in the visible light region. Figure 8 is 2 wt%N-BA@ m X-ray detection limit spectrum of CP scintillation screen, from Figure 8 As can be seen from the figure, the thermoexciton organic glass scintillator has a low thermal conductivity of 37 nGy s -1 The detection limit is much lower than the standard medical X-ray detection limit of 5.5 μGy s -1 , indicating that the material is very responsive to radiation dose, helping to improve image quality and reduce radiation doses received by patients.

[0049] Fig. 9 is 2 wt%N-BA@ m X-ray imaging photos and X-ray imaging resolution diagrams of CP scintillation screens, from Fig. 9 a and Fig. 9 As can be seen in b, the internal structure of the small electronic chip and the hollow metal label can be clearly presented. Fig. 9 c and Fig. 9d. The spatial resolution of the thermoexciton-type organic glass scintillator screen was characterized by line-pair card imaging and modulation transfer function (MTF) calculation. The results show that at MTF=0.3, the spatial resolution of the scintillator screen is 12.5 lp / mm, showing clear imaging potential.

[0050] Fig.10 For the 2 wt% N-BA@ m The stability spectrum of CP scintillator screen under X-ray irradiation, such as Fig.10 As shown, the radiation luminescence intensity of the scintillator screen hardly decreases under long-term repeated switching, showing good radiation stability. Example 2

[0051] A thermoexciton organic glass scintillator material, comprising a glass main material ( m CP-1Br) and hot exciton-type luminescent guest material (N-BA), m The molecular structure of CP-1Br is: .

[0052] m The NMR characterization results of CP-1Br (9, 9'-(5-bromo-1, 3-phenylene) dicarbazole, 9, 9'-(5-bromo-1, 3-phenylene) bis(9H-carbazole)) are as follows: 1 H NMR (400MHz, CDCl3): δ: 8.20–8.13 (m, 4H), 7.89 (d, J = 1.9 Hz, 2H),7.82 (t, J = 1.9 Hz, 1H), 7.57 (dt, J = 8.2, 0.8 Hz, 4H), 7.52–7.45 (m, 4H), 7.38–7.32 (m, 4H).

[0053] 13 C NMR (101MHz, CDCl3): δ: 140.44, 140.26, 128.62, 126.34, 124.09, 123.90, 123.77, 120.74, 120.54, 109.57.

[0054] m The specific preparation method of CP-1Br is as follows:

[0055] based on m CP-1Br and N-BA thermoexciton organic glass scintillator film (2 wt% N-BA@ m The production process of CP-1Br is as follows: S21, take 0.1 g m CP-1Br was mixed with 2 mg of N-BA to obtain a mixture; S22, place the mixture on a 3×3 cm circular silica gel substrate, select an 8 ml×16-well heating block to accurately control the temperature on the heating table, and the melting temperature program is: first heat to 160 °C and keep warm for 5 min, then increase the temperature by 10 °C every 3 min and keep warm for 2 min, and finally heat to 200 °C; S23, waiting for the mixture to be completely melted, stirring until no bubbles are generated, and then keeping the mixture warm for 5 minutes, and then naturally cooling it to room temperature to obtain a thermoexciton organic glass scintillator film.

[0056] Fig.11 It is a thermoexciton organic glass scintillator film 2 wt% N-BA@ m CP-1Br and 2 wt%N-BA@ m The luminescence spectrum of CP, from Fig.11 It can be seen that m The glass scintillator with CP-1Br as the main component also showed an obvious characteristic emission peak near 500 nm, and compared with 2 wt% N-BA@ m CP exhibits significantly stronger radiative luminescence intensity. This is due to the glass host material m The bromine heavy atoms in CP-1Br have stronger absorption of X-rays, resulting in more efficient radioluminescence properties. It can also be seen that the choice of glass host material has an important influence on the scintillation performance of the final glass scintillator. Example 3

[0057] A thermoexciton organic glass scintillator material, comprising a glass main material ( m CP-2Br) and hot exciton-type luminescent guest material (N-BA), m The molecular structure of CP-2Br is: .

[0058] m The preparation route of CP-2Br is as follows: (3) (4) In formula (3), the NMR characterization results of 3-Bromocarbazole are as follows:1 H NMR (400MHz, CDCl3): δ: 8.30–8.27 (m, 2H), 8.15–8.10 (m, 2H), 7.92–7.86 (m, 1H), 7.77 (t, J = 1.9 Hz, 1H), 7.71 (dd, J = 7.9, 2.0 Hz, 2H), 7.57–7.46 (m, 6H), 7.44–7.32 (m, 4H).

[0059] In formula (4), the NMR characterization results of 1, 3-bis(3-bromo-9H-carbazol-9-yl)benzene are as follows: 1 H NMR (400MHz, CDCl3): δ: 8.30-8.27 (m, 2H), 8.15–8.10 (m, 2H), 7.92–7.86 (m, 1H), 7.77 (t, J = 1.9 Hz, 1H), 7.71 (dd, J = 7.9, 2.0 Hz, 2H), 7.57–7.46 (m, 6H), 7.44–7.32 (m, 4H).

[0060] 13 C NMR (101MHz, CDCl3): δ: 140.90, 139.24, 139.04, 131.52, 128.88,126.97, 126.08, 125.39, 125.16, 123.28, 122.55, 120.84, 120.71, 113.19,111.12, 109.85.

[0061] based on m CP-2Br and N-BA thermoexciton organic glass scintillator film (2 wt% N-BA@ m The production process of CP-2Br is as follows: S31, take 0.1 g m CP-2Br was mixed with 2 mg of N-BA to obtain a mixture; S32, place the mixture on a 3×3 cm circular silica gel substrate, select an 8 ml×16-well heating block to accurately control the temperature on the heating table, and the melting temperature program is: first heat to 160 ℃ and keep warm for 5 min, then increase the temperature by 10 ℃ every 3 min and keep warm for 2 min, and finally heat to 220 ℃; S33, waiting for the mixture to be completely melted, stirring until no bubbles are generated, and then keeping the mixture warm for 5 minutes, and then naturally cooling it to room temperature to obtain a thermoexciton organic glass scintillator film.

[0062] Fig.12 It is a thermoexciton organic glass scintillator film 2 wt% N-BA@ m CP-2Br and 2 wt% N-BA@ m The luminescence spectrum of CP, from Fig.12 It can be seen that the thermoexciton organic glass scintillator film 2 wt% N-BA@ m CP-2Br also showed an obvious characteristic emission peak near 500 nm and displayed bright green luminescence, which was significantly higher than that of 2 wt% N-BA@ m CP exhibits significantly stronger radiative luminescence intensity.

[0063] The above describes the specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

[0064] In the description of the present application, it is to be understood that the word 'comprising' does not exclude the presence of elements or steps not listed in the claims. The word 'a' or 'an' preceding an element does not exclude the presence of a plurality of such elements. The simple fact that certain measures are recited in mutually different dependent claims does not indicate that a combination of these measures cannot be used to improve. Any reference signs in the claims should not be construed as limiting the scope.

Claims

1. A thermoexciton organic glass scintillator material, characterized in that: It includes glass host material and hot exciton type high-efficiency luminescent guest material; The glass main body material comprises or ; The hot exciton type high-efficiency luminescent guest material includes , , or .

2. The thermoexciton organic glass scintillator material according to claim 1, characterized in that: R in the glass host material includes H, F, Cl, Br, I or CH3.

3. The thermoexciton organic glass scintillator material according to claim 1, characterized in that: X in the thermoexciton type high-efficiency light-emitting guest material includes N or P.

4. The thermoexciton organic glass scintillator material according to claim 1, characterized in that: R1 in the thermoexciton-type high-efficiency luminescent guest material includes , , , or .

5. The thermoexciton organic glass scintillator material according to claim 1, characterized in that: R2 in the thermoexciton type high-efficiency luminescent guest material includes H, F, Cl, Br or I.

6. A method for preparing a thermoexciton organic glass scintillator material according to any one of claims 1 to 5, characterized in that: The specific steps include: S1, doping the thermoexciton type luminescent guest material into the glass main material to obtain a mixture, wherein the mass ratio of the thermoexciton type luminescent guest material to the glass main material is 0.001%-6%; S2, placing the mixture on a silica gel substrate to melt, the melting temperature program is: first heating to 160 ° C and keeping it for 5 minutes, then heating by 10 ° C every 3 minutes until the temperature reaches the preset melting temperature; S3, the mixture is completely melted, stirred until no bubbles are generated, and then kept warm for 5 minutes, and then naturally cooled to room temperature to obtain a thermoexciton type organic glass scintillator film material.

7. The method for preparing the thermoexciton organic glass scintillator material according to claim 6, characterized in that: In S1, the mass ratio of the thermoexciton type luminescent guest material to the glass host material is 0.001%, 0.01%, 0.1%, 0.5%, 2%, 4% or 6%.

8. The method for preparing the thermoexciton organic glass scintillator material according to claim 6, characterized in that: In S2, the melting heating device is a heating block.

9. The method for preparing the thermoexciton organic glass scintillator material according to claim 6, characterized in that: In the S2, the melting temperature is 180-220°C.

10. Use of the thermoexciton organic glass scintillator material according to any one of claims 1 to 5 in X-ray imaging.

Citation Information

Patent Citations

  • Host-guest doped luminescent material taking iodo-carbazole derivative as host and preparation and application method thereof

    CN113122240A

  • Molecular glass scintillator material and preparation method and application thereof

    CN116218520A

  • Charge transfer type organic eutectic material, scintillator eutectic film and preparation method and application thereof

    CN118444360A